Relationship between Change in Behavior Pattern and Change in Blood Pressure - SHIRASAWA, Akira; IIJIMA, Kenichi; YAMASHITA, Kazuya (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1996)
We examined the relationship between the change to a type A behavior pattern and the changes in systolic blood pressure (SBP) and diastolic blood pressure (DBP) in subjects who work in T town communities. A screening test was performed to determine which subjects had a type A behavior (Tagawa et al.). Between 1994 and 1995 there were 10 subjects in whom the pattern changed from type B2 to type A2 (Changed Group) and 11 subjects in whom the pattern stayed in type B2 (Unchanged Group). The rate of change to type A score [(type A score in 1995-type A score in 1994)/type A score in 1994×100] was correlated with the rate of change in SBP [(SBP in 1995-SBP in 1994)/SBP in 1994] and DBP [(DBP in 1995-DBP in 1994)/DBP in 1994×100]. In the Changed Group, SBP and DBP levels in 1994 were significantly higher than those in 1995. However, in the Unchanged Group, there were no significant differences in SBP or DBP level between 1994 and 1995. Furthermore, there were no significant differences in SBP or DBP level between the Changed and Unchanged Groups in 1994 and 1995. Our results suggest that type A behavior and blood pressure are closely related.